Comparison of sepsis-associated acute kidney injury with different degrees and causes reveals patterns in mitochondrial metabolism and immune infiltration changes - Nan Yuan; Jianwen Chen; Feng Luo; Zhenyu Fang; Mengjie Huang; Jiaona Liu; Xiangmei Chen; Congjuan Luo (Scientific Reports)
Abstract Sepsis-associated acute kidney injury (SA-AKI) is a common complication in critically ill patients, characterized by high morbidity and mortality rates. It remains primarily treated with supportive and nonspecific therapies because of the absence of effective diagnostic biomarkers and therapeutic targets. This study utilized cecal ligation and puncture (CLP) and intraperitoneal injection of lipopolysaccharide (LPS) to create a murine model of SA-AKI, simulating various degrees of severity and aetiologies. Renal transcriptome sequencing was performed, followed by extensive bioinformatic analyses, including gene expression trend analysis using the Mfuzz package, weighted gene co-expression network analysis (WGCNA), protein–protein interaction (PPI) networks, and Cibersort immune infiltration analysis, to uncover key molecular changes in SA-AKI. Transcriptome analysis revealed that SA-AKI induces mitochondrial dysfunction and metabolic disturbances. As the severity of SA-AKI increases, immune-inflammatory activity becomes more pronounced, along with significant metabolic dysfunction. Variations in immune cell infiltration between different aetiologies of SA-AKI suggest distinct immune response patterns and timing. Six hub mitochondrial differentially expressed genes (MitoDEGs) related to SA-AKI severity were identified and validated, showing significant associations with immune cell infiltration. These findings provide valuable insights into SA-AKI pathogenesis and the exploration of therapeutic targets.